2011
DOI: 10.1063/1.3660325
|View full text |Cite
|
Sign up to set email alerts
|

Water adsorption on graphene/Pt(111) at room temperature: A vibrational investigation

Abstract: Water interaction with quasi-freestanding graphene deposited on Pt(111) has been investigated by using vibrational spectroscopy. Loss measurements show that water molecules dosed at room temperature can dissociate giving rise to C-H bonds. The formation of the C-H bonds strongly attenuates the optical phonons of the graphene sheet. On the other hand, at 100 K water has been found to adsorb only in molecular state. Present findings should be taken into account in engineering graphene-based devices which should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 57 publications
2
27
0
Order By: Relevance
“…5. The features we observe near 0.4 eV (2900 cm -1 ) are due to C-H vibrations bands caused by water absorption on graphene [16]. The peaks in mid-IR near 0.2 eV, were previously observed in single and multilayer graphene [17] and were associated with different band structures of multilayer graphene flakes.…”
Section: Fourier Transform Infra Red Spectroscopymentioning
confidence: 72%
“…5. The features we observe near 0.4 eV (2900 cm -1 ) are due to C-H vibrations bands caused by water absorption on graphene [16]. The peaks in mid-IR near 0.2 eV, were previously observed in single and multilayer graphene [17] and were associated with different band structures of multilayer graphene flakes.…”
Section: Fourier Transform Infra Red Spectroscopymentioning
confidence: 72%
“…On the latticemismatched graphene/Ru(0001) interface, the corrugation of the graphene overlayer induces site selectivity for H adsorption in dimers. Instead, no dimer formation has been reported to occur in the nearly-flat, multidomain graphene/Pt(1 1 1) interface [54].…”
Section: Resultsmentioning
confidence: 99%
“…151 Rafiee et al studied the wetting of graphene sheets by water and reported that graphene sonicated in water, acetone or a combination of water and acetone showed different contact angles with water droplet ranging from super-hydrophobic to super-hydrophilic behavior. 152 The molecular arrangement of water on graphene surface has also been studied by Kimmel et al who deposited thin films of H 2 O or D 2 O on graphene substrate at temperatures ranging from 20 to 152 K. It was found that ice layers formed on the graphene surface, showing significant wetting at 135 K. 153,154 At higher temperatures, these ice layers de-wet the surface forming ice crystals. The presence of a vacancy changed the adsorption energy of water for graphene.…”
Section: Physisorption Of Water On Nanostructured Carbon Materialsmentioning
confidence: 96%